ATTITUDE OF SECONDARY SCHOOL TEACHERS TOWARDS NEP 2020 WITH REFERENCE TO COMPONENTS OF SCHOOL EDUCATION - Neelofar; G. Suneetha Bai (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The article was focused to investigate teachers’ attitude towards NEP 2020 with reference to components in School Education sector and also to get about the Teachers practices to execute NEP 2020 in schools, survey method was adopted for the investigation on a sample of 180 and Likert type questionnaire developed to collect data. It is analyzed statistically computing such as Mean, SD and t- test. The investigation revealed insignificant difference in the attitude among secondary school teachers towards NEP 2020 with respect to locality and management. Whereas variation was significant with gender.